KERANGKA TEORETIS KETERAMPILAN MENDENGARKAN AKTIF DI ERA DIGITAL: MODEL INTEGRATIF UNTUK INTERVENSI SISWA SMA - Rika Rahayu; Uman Suherman; Ibrahim Al-Hakim (IKIP Siliwangi, 2026)
The digital era has transformed the communication landscape of Indonesian adolescents. The phenomena of phubbing and technoference have become serious barriers to the development of active listening skills (ALS). Data from APJII (2024) shows thatinternet penetration among adolescents reaches 87.02% with usage duration of 6-10 hours per day. This article develops a